SAG4 DNA and Peptide Vaccination Provides Partial Protection against T. gondii Infection in BALB/c Mice - Zhou, Jian; Wang, Lin (Frontiers in Microbiology, 2017)
Toxoplasma gondii can lead to congenital infections in human. Surface antigen protein 4 (SAG4) of T. gondii is a potential stimulator for humoral and cellular immune responses. In the present study, a DNA vaccine encoding SAG4 from T. gondii was constructed and used to immunize BALB/c mice with peptide to evaluate the protective efficacy of the vaccine. The productions of IgG antibodies and cytokines (gamma interferon) from the vaccine (pSAG4/peptide) group were significantly higher than pSAG4 or peptide groups. After a lethal challenge by 1 × 104 tachyzoites from the I strain (RH), the survival time of mice immunized by pSAG4/peptide was longer than that of pSAG4 or peptide immunized mice or control mice. Moreover, after challenging by 20 cysts of the II strain (PRU) of T. gondii, the number of brain cysts from pSAG4/peptide vaccinated mice was only 31% of the number in PBS injected mice. The findings suggested the SAG4 DNA vaccine with peptide led significant immune responses and improved the protection against T. gondii challenges.